Tortilla Flat Movie Still - MGM:::Creator::::::::::::
Pilon (Spencer Tracy), Dolores 'Sweets' Ramirez (Hedy Lamarr), and Danny Alvarez (John Garfield) in MGM's adaptation of John Steinbeck's novel. RESTRICTED USE Digital copy only. No hard copy.